Abundance and Spatial Dispersion of Rice Stem Borer Species in Kahama, Tanzania. Issue 1 (25th September 2015) - Leonard, Alfonce; Rwegasira, Gration M.
Abstract : Species diversity, abundance, and dispersion of rice stem borers in framer's fields were studied in four major rice growing areas of Kahama District. Stem borer larvae were extracted from the damaged tillers in 16 quadrants established in each field. Adult Moths were trapped by light traps and collected in vials for identification. Results indicated the presence of Chilo partellus, Maliarpha separatella, and Sesamia calamistis in all study areas. The most abundant species was C. partellus (48.6%) followed by M. separatella (35.4%) and S. calamistis was least abundant (16.1%). Stem borers dispersion was aggregated along the edges of rice fields in three locations (wards) namely: Bulige, Chela, and Ngaya. The dispersion in the fourth ward, Kashishi was uniform as established from two of the three dispersion indices tested. Further studies would be required to establish the available alternative hosts, the extent of economic losses and the distribution of rice stem borers in the rest of the Lake zone of Tanzania.